SEMINAR ONLINE PERENCANAAN KEUANGAN SYARIAH - Siti Suherni; Isfandayani Isfandayani; Fajri Ryan Isnandar (Al-Ihsan: Journal of Community Development in Islamic Studies, 2022)
Indonesia confirmed its first case of infection with the corona virus that causes Covid-19 in early March 2020. The decline in economic growth due to the Covid-19 pandemic can trigger impacts on other aspects such as social aspects. The role of the government and educators is needed to carry out outreach in the economic field such as financial planning during this covid outbreak. The method used in this community service is outreach to the public regarding the importance of sharia financial planning. The results in this study are to add knowledge to the community regarding Islamic financial planning.